Formal and informal social safety nets : growth and development in the modern economy - Ashraf, Mohammad; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
In Formal and Informal Social Safety Nets , Ashraf analyses the role of social safety nets in a time when our global economy threatens our way of life, as entire cities such as Detroit are declared bankrupt.
Keywords: Political economy; Microeconomics; Welfare economics; Public finance; Economic policy; Economic growth